Negative Predictors of Tooth Extraction in the Management of Odontogenic Sinusitis in a Japanese Patient Population: A Retrospective Study - Kazuhiro Hirasawa; Koji Otsuka; Renako Tomaru; Naoki Ikehata; Kiyoaki Tsukahara (International Archives of Otorhinolaryngology)
Introduction There are no clear guidelines for deciding between endoscopic sinus surgery and tooth extraction for the treatment of odontogenic sinusitis. Furthermore, tooth extraction does not necessarily improve sinusitis and eventually results in additional endoscopic sinus surgery.